Experimental study of an oscillator ensemble with global and nonlinear coupling - Zhanabaev, Z. Zh.; Temirbayev, A. A.; Tarasov, S. B.; Nalibayev, Y. D. (Publishing House of the KarSU named after E.A.Buketov, 2011)
We analyze collective dynamics of a population of electronic limit-cycle oscillators with a linear or nonlinear phase shifting unit in the global feedback loop. We conduct both physical experiment and mathematical modeling. Besides the standard Kuramoto synchronization transition in case of linear coupling we demonstrate a transition to a self-organized quasiperiodic state, predicted in [M. Rosenblum and A. Pikovsky, Phys. Rev. Lett., 98, 064101 (2007)]. In this state frequency of oscillators differs from the frequency of the mean field and dependence of the order parameter on the coupling strength is not monotonic. We demonstrate a good correspondence between the experiment and previously developed theory.
Keywords: oscillator ensemble; self-organized quasiperiodic state; frequency; synchronization transition; globally coupled system